A parabolic trough solar collector as a solar system for heating water: a study based on numerical simulation - Ghodbane, Mokhtar; Boumeddane, Boussad (جامعة الوادي - university of el oued, 2017)
This paper is an optical and thermal study of a small model of a parabolic trough solar collector (CTP), which will be used to heat tap water, in the winter, at Guemar location, (El-Oued, Algeria). A mathematical model was presented based on the energy balance equation applied to the absorber tube; this model was solved by the finite difference method. A computer program based on MATLAB was developed to solve the problem. The results show that the thermal efficiency of the concentrator can attend a high value of more than 61%, while the fluid outlet temperature can reach 343 K.
Article Article
Keywords: olar thermal, parabolic trough collector, outlet temperature, Tap water, numerical analysis